2019
DOI: 10.21727/rpu.v10i1.1751
|View full text |Cite
|
Sign up to set email alerts
|

Manejo cirúrgico do paciente submetido à terapia anticoagulante oral

Abstract: ResumoIntrodução: bem se sabe que quando um paciente está submetido à terapia anticoagulante, seus níveis de coagulação ficam alterados, aumentando o risco de intercorrências transoperatórias. Dessa forma, tem-se levantado muitos questionamentos, tanto na área médica como na odontológica, quanto à melhor conduta a se seguir para a realização de um tratamento cirúrgico-odontológico seguro em pacientes anticoagulados. Com o objetivo de realizar uma revisão de literatura abordando as peculiaridades inerentes ao a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…were cases that after 02 days of extraction of a premolar and 05 days of medication break, it could generate an acute myocardial infarction.DASILVA et al (2019), based on the critical reading and study of articles that were based on evidence of a high scientific nature, decided to outline a protocol for preoperative guidelines, ordering tests, International Normalized Ratio (INR) parameters, determination of the pause or permanence of the therapy, orientations before the procedures and their complexity, as well as the use of hemostatic techniques and postoperative precautions.LABADIB et al (2018), since its approval, other types of direct-acting oral anticoagulants (DOACs) have become increasingly prescribed, more precisely gantran, apixaban, rivaroxaban, offering an alternative to what are said to be disadvantages of warfarin. A study done by the Royal Dental Hospital of Meuborn based on bleeding profiles similar to the use of DOACs or warfarin, it was concluded that the results of the study suggest that extractions can be performed without ceasing the direct oral anticoagulant, with a low incidence of complications bleeding if local hemostatic measures are applied.…”
mentioning
confidence: 99%
“…were cases that after 02 days of extraction of a premolar and 05 days of medication break, it could generate an acute myocardial infarction.DASILVA et al (2019), based on the critical reading and study of articles that were based on evidence of a high scientific nature, decided to outline a protocol for preoperative guidelines, ordering tests, International Normalized Ratio (INR) parameters, determination of the pause or permanence of the therapy, orientations before the procedures and their complexity, as well as the use of hemostatic techniques and postoperative precautions.LABADIB et al (2018), since its approval, other types of direct-acting oral anticoagulants (DOACs) have become increasingly prescribed, more precisely gantran, apixaban, rivaroxaban, offering an alternative to what are said to be disadvantages of warfarin. A study done by the Royal Dental Hospital of Meuborn based on bleeding profiles similar to the use of DOACs or warfarin, it was concluded that the results of the study suggest that extractions can be performed without ceasing the direct oral anticoagulant, with a low incidence of complications bleeding if local hemostatic measures are applied.…”
mentioning
confidence: 99%